EPIDEMIOLOGY AND COMPLICATIONS OF COVID-19 (Multidisciplinary Journal of Science and Technology, 2025)
The liver is a vital organ. The liver has many functions in the human body. Participates in the reactions of the immune system. In addition, it determines the overall level of resistance to infections and is responsible for the production of antibodies to fight viruses and bacteria. Liver diseases are the most common in the world. Especially in the context of the COVID-19 pandemic. World Health Organization February 11, 2020.